Support to responsive parenting through communication tools. (30th September 2020) - Jankovic, S; Matijevic, D; Grujicic, A; Markovic, M; Stefanovic, N; Kovacevic, N; Tamburkovski, G
Abstract: Issue: Counselling unit for positive parenting "Halobeba" has been established at Institute of Public Health of Belgrade with support of UNICEF in order to enable continuum of mother and child health care. Availability of information on child care and development was noticed as significant factor for parental confidence and practice. Description of the problem: Trained nurses provide responses to parental questions through 24/7 phone and e mail communication to assist in problem solving and offer emotional support. Nurses are skilled in active listening, proper questioning, counselling and effective encouragement. Free mob app on breastfeeding was developed as knowledge base for parents. New interactive mob app was recently launched as parenting tool for child health and development monitoring. Results: Since 2002, more than 1, 700, 000 responses were provided through phone communication and over 20, 000 via email and number of beneficiaries has increased over the years. Most common topics were about breastfeeding, introducing solid food, treatment of fever and respiratory infections, gastrointestinal problems, injuries, immunization, and developmental milestones. Less than 15% of cases were referred to pediatric clinic. Level of parental overall satisfaction was very high and availability and effectiveness of service were especially valued as well as nurses communication skills. Lessons: Family centered service that corresponds to caregivers needs is effective approach to support nurturing care for young children. Personalized M-health tools make child care more accessible and build capacities of caregivers. Key messages: Sending consistent and trusted messages through different communication channels contribute to enhancing users' knowledge and skills. Knowledgeable and responsive caregivers properly interpret child's needs, respond appropriately, facilitate the child's social and emotional development, and provide proper care.